Pelatihan Pemeliharaan Lingkungan dengan Konsep Biopori bagi Mahasiswa - Mulyana, Ahmad; Irawan, Enjang Pera (Universitas Nusantara PGRI Kediri, 2023)
Areas such as urban areas have relatively low water absorption. This is due to the imbalance between the pace of development and the availability of green open space. This condition eventually causes problems such as easy flooding, the difficulty for the community to obtain groundwater reserves, and the biological balance that is increasingly difficult to realize. Referring to these conditions, the solution that the author offers is to organize environmental maintenance training with the biopore concept for students. The target of this training is 30 participants from Mercu Buana University. The methods used in this training are through lectures, interactive discussions, and conducting simulations (practice). These results indicate that the students are very enthusiastic about participating in this training and are serious about practicing biopore making activities. In training, students were also invited to practice making biopore in the community, precisely at RT 001 and RT 003 RW 001, Meruya Selatan, Kembangan District, West Jakarta. The benefits that can be felt from making biopore include preventing flooding, being a dumping ground for organic waste, fertilizing plants, and improving air quality. After participating in this program, students are expected to become agents of change in their respective environments. In addition, through this activity, it is hoped that students can become examples and movers in environmental care in their respective regions.